Evaluation of pharmacological properties, phytochemistry, and medicinal uses of Baccharoides guineensis - Alfred Maroyi (Journal of Applied Pharmaceutical Science, 2020)
The leaves, roots, and/or tubers of Baccharoides guineensis are used as traditional medicines in West Africa. This study is aimed to evaluate the pharmacological properties, photochemistry, and medicinal uses of B. guineensis. The results of this study are based on data derived from online databases such as Scopus, Google Scholar, PubMed, ScienceDirect, and MEDLINE and pre-electronic sources such as scientific publications, theses, books, dissertations, book chapters, and journal articles. This study revealed that the leaves, roots, and/or tubers of B. guineensis are widely used as anthelmintic, snakebite antidote, and ethnoveterinary medicine and as traditional medicine for toothache, gastrointestinal problems, jaundice, malaria, female, and male infertility. Phytochemical compounds identified from the species include anthraquinones, ceramide, fatty acids, flavonoids, glycerol esters, sesquiterpene lactones, steroids, stigmatanes, sucrose esters, and triterpenoids. The pharmacological research revealed that B. guineensis extracts and phytochemical compounds isolated from the species have antioxidant, anthelmintic, antiangiogenic, antibacterial, antiplasmodial, antiproliferative, antitrypanosidal, clonogenic, and antifungal activities. The future research on B. guineensis should focus on the possible biochemical mechanisms of both the crude extracts and phytochemical compounds including the toxicological, in vivo, and clinical studies to corroborate the traditional medicinal applications of the species.
Keywords: Asteraceae, Baccharoides guineensis, Compositae, indigenous pharmacopeia, traditional medicine.